Pelatihan Slide Navigasi Sebagai Media Pembelajaran Untuk Para Guru - Muhammad Fauzi; Yudi Yudi; Fuadaturahmah Fuadaturahmah (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
Power Point is an application from Microsoft which is intended as a presentationmedia. Basically, many presentation media today are being developed by other vendors. Even so, PowerPointt is no less competitive. This application is considered as one application that is very friendly for its use. The PowerPoint application was developed by Microsoft in their office application package beside that Microsoft Office in addition to Microsoft Word, Excel, Access, and several other programs. This application is widely used, especially by offices and business people, educators, students, and trainers tomake presentations, both by students, students, teachers, and companies. With this program, users can display a variety of text, images, and videos. Therefore, it is important to apply power points in the field of education as a medium for student learning. Keywords: PowerPoint, Learning Media, Education.